Analisis Triple-Bottom-Line pada Usaha Distilasi Nilam (Studi Kasus dari Desa Bela Mamuju) - Irmawati Irmawati (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
The patchouli industry is one of the agricultural sectors that has various potential for good and profitable agribusiness development. The success of the agricultural industry can be achieved through development. However, on the other hand, economic development, particularly through industrial development (Such as Patchouli Distillation), can threaten the sustainability of social development, potentially triggering environmental damage. These three pillars significantly impact the welfare of the community, so a concept is needed that supports the implementation of the relationship between them. This study aims to explore the social, economic, and environmental impacts of the patchouli distillation industry. For this reason, qualitative descriptive analysis is needed to explore these three aspects of the patchouli distillation industry. Data were collected through observation, interviews, and documentation. Furthermore, quantitative data analysis was conducted to evaluate the feasibility of the patchouli distillation industry by employing the Revenue Cost Ratio (R/C Ratio) approach. The study's results showed that the social impact of the patchouli distillation industry in Bela Village, Tappalang District, did not harm the surrounding community. Viewed from the aspect of public health, they did not feel disturbed and there were no attacks of any disease caused by the distillation industry, but instead had a good impact on social conditions in terms of community behavior. From an economic perspective, the patchouli distillation industry has a significant impact on the income of both entrepreneurs and employees, as well as the community of patchouli farmers surrounding the industry. The results of the study on the distillation industry from an environmental perspective show that the industry does not have a negative impact on the environment, as the liquid waste produced is properly managed through drainage systems. Therefore, the government needs to implement structured extension programs for farmers, enabling them to master various innovations and technologies as well as to access a wide range of financing sources in the agricultural sector.